A Metodologia Ativa (ABP) no ensino das ciências ambientais: projetos sustentáveis com produtos técnicos de hortas mandalas agroecológicas nas escolas - Lessa, Ana Carolina Vilar (2021)
The agroecological mandalas gardens are social technologies that allow production of animal and vegetable food following the agroecology principles, that means, no use of pesticides and prioritizing environmental health in a sustainable way. The social contributions of this technology present two perspectives, one of which is educational, with the use of the agroecological mandala garden implemented as a pedagogical tool through ABProj, allowing the classroom to contextualize the problems involved in the food production chain, which begins in the countryside and permeates technological, financial and social issues. And another perspective, related to food security discussion, nutrition improving, eradicating hunger and promoting sustainable agriculture, as announced by the United Nations-UN in SDG-2 of Agenda 2030. In this context, this dissertation aims to develop sustainable agriculture technology projects with agroecological mandalas gardens, from the active methodology of project-based learning (ABP), as a contribution to the teaching and learning processes for the instruction of environmental sciences. This research had an analytical bibliographic nature, with data and survey information, from available records, accomplished through consultation, analysis and reflection on specific topics, namely: environmental sciences, sustainable rural development, agroecology, social technologies, pesticides, food sovereignty, active methodologies. The results confirm the benefits of adopting agroecological mandala gardens as social technologies capable of promoting food sovereignty and security in family farming communities, as indicated by the Sustainable Development Goals. In addition, the importance of implementing agroecological mandalas gardens as pedagogical tools, through project-based learning and their potential to train students with critical capacity to perceive and act on social, economic, political and environmental issues in their community was found. Finally, the feasibility of projects for agroecological mandalas gardens was highlighted as tending towards the preservation of nature elements, while providing the improvement of income and environmental health in the served communities.